PENGARUH LATIHAN CORE STABILITY STATIS (PLANK AND SIDEPLANK) TERHADAP KESEIMBANGAN TUBUH PADA PEMAIN PS IKIP MATARAM TAHUN 2019 - Ismail Marzuki; Soemardiawan Soemardiawan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
he focus of the problem in this study was during the training and competition of the PS players. IKIP Mataram is lacking in passing, dribbling, control, shooting, because it is not good in body balance training in body charge, it is easy to fall, as well as in passing, dribbling, control, shooting skills, and therefore the exercise of Static Core Stability Exercise (Plank) And Side Plank) to improve the body balance of PS players. IKIP Mataram. The formulation of the research problem is "Are there any Effects of Static Core Stability Exercise (Plank and Side Plank) on Body Balance in PS IKIP Mataram Players in 2019". PS IKIP Mataram Players in 2019 ".. The research design used was experimental research" One-Group Pretest-posttest Desaign ". This experiment still has external variables that influence the formation of the dependent variable. So the results of experiments which are dependent variables are not solely influenced by the independent variables. The sampling technique uses a population study of 20 players. The results of t-test analysis concluded that "The Effect of Static Core Stability Exercise (Plank and Side Plank) on Body Balance in PS IKIP Mataram Players in 2019". This situation is supported by t-test analysis which results in t-counts greater than t-tables (10.30> 1,729), so that the null hypothesis (Ho) is rejected. The Body of Mataram IKIP PS Players in 2019 ". Ha was given, there was an influence on the influence of Static Core Stability Exercise (Plank and Side Plank) on Body Balance in PS IKIP Mataram Players in 2019